The Application Of Language Learning Strategies In Japanese Language Learning - Lensun, S F (Journal of Educational Method and Technology, 2018)
The Educators must place their students as people who naturally have experience, knowledge, desires, and thoughts that can be used to learn, both individually and in groups. All language learning strategies have the main goal of increasing one's ability to speak. The choice of teaching and learning strategies language learning strategies must be based on the consideration of placing students as subjects of learning who not only passively accept what is conveyed by educators. Teaching Japanese especially kanji using various learning strategies makes it easy for Japanese learners especially in learning Japanese letters/starch. Language learning strategies/learning strategies used are direct strategies and indirect strategies. Direct Strategy is a strategy that is directly related to foreign language learning. That is directly related to language in various tasks and situations, consisting of (1) memory strategies, (2) cognitive strategies, and (3) compensation strategies. Indirect Strategies in language learning are strategies that indirectly support language learning through ways such as the focus of learning, planning, assessment, acquiring learning opportunities, avoiding anxiety in learning, working with others. This strategy consists of three elements, namely (1) metacognitive strategies that are tasked with coordinating the learning process, (2) affective strategies that are in charge of regulating emotions, and (3) social strategies that are tasked with fostering cooperation with others in the learning process. This study aims to obtain scientific data the process of increasing mastery of Japanese letters/kanji by applying Language learning strategies direct strategies and indirect strategies. The method used in this study is an action research method. Data from the research results were analyzed qualitatively and quantitatively. Referring to the model developed by Kemmis and Mc. Taggart is a spiral model. The research method used is the method of Action research with four steps, namely (planning, implementation, observation, and reflection). Use of the application of Language Learning Strategies in Kanji learning among others: (1) the development of writing and Kanji reading skills through meaningful learning experiences, (2) Kanji learning is more systematic and creative both individually and in collaboration with friendsKeywords: Language, learning, strategies, Kanji